Drawings and projects, Jo Noero and architectural practice in South Africa - Samanta Bartocci (Festival dell'Architettura Magazine, 2022)
Works constructed, designed, drawn by hand and redesigned after they have been built, have given life to a pathway, but above all, a succession of diversities, precisely because architecture is not a specialist domain but a meeting-point between different forms of human creativity. Noeroarchitects’ (South Africa) professional work and the visions of a progressive repertory of architectural drawings by Jo Noero indicate the role of drawing as an instrument for portraying not just facts but also desires. Drawing is for Noero common writing, it is the sense of knowing by doing, which protects him from the abstractness of the diagrams and stylistic figures of his profession as an architect; drawing has nurtured the complexity of his vision and the corresponding relations between architecture and the strength of the purpose for which it is built.